Process for synthesizing polyether ether ketone by using complexed porous sodium carbonate

CN122685875BActive Publication Date: 2026-10-09BLUE OCEAN NEW MATERIALS (TONGZHOU BAY) CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611199532.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-09
Estimated Expiration
2046-08-10

AI Technical Summary

Technical Problem

(1)反应物局部过浓引发副反应:传统工艺多采用一次性加料方式,固相成盐剂与液相单体、溶剂接触时易出现局部浓度过高的现象,不仅会引发醚化、酚类氧化等副反应,生成的副产物还会附着在反应位点表面,进一步阻碍主反应进行;

Benefits of technology

复配多孔碳酸钠突破了单一孔结构材料“高比表面积与低传质阻力难以兼得”的固有瓶颈,可在成盐反应阶段同时实现高活性位点密度与高效传质效率,进而通过均一的成盐产物提升后续聚合反应的产物品质。致密碳酸钠仅依靠颗粒外表面发生成盐反应,传质阻力极大,成盐生成的水易在颗粒表面形成水合物钝化层(裹结效应),反应速率随反应进行持续衰减,最终成盐转化率低、产物均一性差;轻质碳酸钠虽经碳酸氢钠煅烧分解形成多孔结构,但孔道无序,以盲孔和半连通孔为主,有效反应深度仅局限于颗粒表层,传质改善幅度有限,整体成盐效率提升不显著;单一介孔碳酸钠虽具备高比表面积与丰富活性位点,但孔径细小导致内扩散阻力大,成盐过程中生成的CO2易在孔道内形成气阻,原位生成的酚钠向外扩散速率受限,反应中后期速率衰减明显,颗粒深部的活性位点无法充分利用,成盐转化率存在明确上限;单一大孔碳酸钠孔道贯通、内扩散阻力小,CO2副产物可快速逸出,成盐反应启动快、位点利用率高,但受限于较低的比表面积,总活性位点数量不足,整体成盐反应容量存在明确上限。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122685875B_ABST
    Figure CN122685875B_ABST
Patent Text Reader

Abstract

The application discloses a process for synthesizing polyether ether ketone by using compounded porous sodium carbonate, and relates to the technical field of polyether ether ketone.The raw materials such as hydroquinone and a salting agent are premixed under the protection of nitrogen, solid-phase materials and molten diphenyl sulfone are introduced into a reaction kettle to complete salting and polymerization, pulse stirring is combined, temperature control is realized in stages by using an intermittent method or a continuous method, and the salting agent is special compounded porous sodium carbonate.The application can improve salting and polymerization efficiency, shorten the synthesis time, narrow the molecular weight distribution of the product, improve the mechanical properties of the polyether ether ketone, and is suitable for intermittent / continuous industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyether ether ketone (PEEK) technology, and more specifically to a process for synthesizing PEEK using a compound porous sodium carbonate. Background Technology

[0002] Polyetheretherketone (PEEK), a semi-crystalline special engineering plastic, possesses extremely high mechanical strength, excellent thermal stability, chemical corrosion resistance, friction and wear resistance, and water decomposition resistance. It also has good melt processing properties and can be prepared into various products through injection molding, extrusion molding, and machining. It has been widely and critically applied in high-end fields such as aerospace, automotive manufacturing, electronics, biomedicine, and petrochemicals, and is one of the special engineering plastics with the best comprehensive performance currently available.

[0003] The mainstream industrial method for preparing polyetheretherketone (PEEK) is nucleophilic substitution polymerization, using 4,4'-difluorobenzophenone (DFBP) as the fluorinated monomer, hydroquinone (HQ) as the phenolic monomer, sodium carbonate or potassium carbonate as the salt-forming agent, and diphenyl sulfone (DPS) as the high-temperature solvent. The process involves a salt-forming reaction followed by polymerization. The core reaction steps are two-step: First, hydroquinone reacts with the salt-forming agent in a heterogeneous salt-forming reaction, producing sodium hydroquinone, carbon dioxide, and water. The water needs to be removed promptly to promote the forward salt-forming reaction. Second, sodium hydroquinone reacts with 4,4'-difluorobenzophenone in a nucleophilic substitution polymerization reaction during heating, gradually forming a PEEK polymer chain.

[0004] To optimize the synthesis efficiency and product performance of polyetheretherketone (PEEK), numerous improvements have been made in existing technologies. For example, Chinese invention patent CN114437338B discloses a method for synthesizing PEEK, and Chinese invention patent CN115612092A discloses a method for synthesizing PEEK. Both methods involve pre-preparing a sodium hydroquinone intermediate and then polymerizing it with 4,4'-difluorobenzophenone, attempting to reduce side reactions during polymerization by completing the salt-forming reaction earlier. Other technologies improve the molecular weight and distribution of PEEK by adjusting parameters such as reaction temperature, stirring rate, and raw material ratio. However, even with these advancements, the heterogeneous synthesis process using sodium carbonate as a salt-forming agent still faces core technological bottlenecks. The problems of low salt-forming reaction efficiency and long reaction time remain unresolved. Furthermore, incompletely reacted hydroquinone and its oxidation products introduce impurities, significantly reducing the thermal stability and mechanical properties of PEEK products, while also leading to a wide molecular weight distribution of the polymerized products, affecting batch-to-batch stability.

[0005] Research has revealed that the low efficiency of the heterogeneous salt formation reaction of polyetheretherketone (PEEK) stems from defects in mass transfer and mixing within the solid-liquid heterogeneous reaction system, specifically manifested in the following aspects: (1) Local overconcentration of reactants triggers side reactions: Traditional processes often use a one-time feeding method. When solid salt-forming agents come into contact with liquid monomers and solvents, local overconcentration is likely to occur. This not only triggers side reactions such as etherification and phenol oxidation, but the generated byproducts also adhere to the surface of the reaction sites, further hindering the main reaction. (2) Insufficient mass transfer efficiency of traditional stirring: Conventional mechanical stirring has limited shear force and mixing capacity, making it difficult to achieve uniform dispersion of solid salt-forming agent particles in molten diphenyl sulfone solvent. Stirring dead zones are easily formed in the reactor, resulting in some materials being unable to participate in the reaction, and the overall reaction efficiency is greatly reduced. (3) Limited reaction rate at solid-liquid interface: Sodium carbonate is a dense solid particle or a disordered open-pore structure with insufficient specific surface area. The reaction sites with hydroquinone are limited. The reactants need to overcome mass transfer resistance to diffuse to the interface, and the reaction products also need to diffuse from the interface into the solvent. The large mass transfer resistance leads to a low reaction rate at the interface. At the same time, if the water generated by the salt formation reaction cannot be removed from the particle surface in time, it will form hydrates with sodium carbonate, which will produce a "binding and passivation" effect on the sodium carbonate particles, blocking the subsequent reaction. Ultimately, the salt formation reaction is incomplete, and the remaining unreacted raw materials will directly affect the uniformity of the subsequent polymerization reaction.

[0006] Furthermore, existing technologies have limited research on salt-forming agents. The physical morphology of conventional dense sodium carbonate is unsuitable for the mass transfer requirements of heterogeneous reactions. Light sodium carbonate, typically obtained by calcining sodium bicarbonate, has a random porous structure with numerous blind pores, limiting its mass transfer enhancement. Optimization of mixing methods for heterogeneous reaction systems is limited to adjusting conventional stirring parameters, failing to fundamentally address the issues of uneven solid-liquid mixing and low mass transfer efficiency. Therefore, developing a polyetheretherketone (PEEK) synthesis process that can overcome the mass transfer bottleneck in heterogeneous reactions, improve salt-forming reaction efficiency, and reduce side reactions, thereby achieving efficient, high-performance, and controllable synthesis of PEEK, has become a pressing technical challenge in this field. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a process for synthesizing polyether ether ketone using compound porous sodium carbonate, which can improve salt formation and polymerization efficiency, shorten synthesis time, narrow the molecular weight distribution of the product, improve the mechanical properties of polyether ether ketone, and the process is suitable for batch / continuous industrial production.

[0008] The technical solution of this invention is as follows: A process for synthesizing polyetheretherketone (PEEK) using compound porous sodium carbonate involves the following steps when using a batch method: Hydroquinone, compound porous sodium carbonate, and 4,4'-difluorobenzophenone are pre-mixed in a solid phase under nitrogen protection. The uniformly dispersed solid material is then sequentially introduced into a reactor along with molten diphenyl sulfone. The reactants are first heated to 160-200°C with stirring at 30-80 rpm and held at this temperature for 0.5-1.5 hours. Subsequently, the temperature is increased to 180-200°C. The polymerization reaction is carried out at 20℃ for 0.5-1.5 hours, then heated to 240-270℃ for 0.5-2 hours, then heated to 260-290℃ for 0.5-2 hours, and finally heated to 300-320℃ for 1-3.5 hours to complete the polymerization reaction. During this process, pulse stirring is applied every 10-30 seconds, each lasting 10-90 seconds. When applying the pulse, the stirring speed is adjusted to 40-120 rpm to generate instantaneous turbulence. When synthesizing polyetheretherketone (PEEK) using a continuous method, hydroquinone and a compound porous sodium carbonate are premixed in a solid phase under nitrogen protection. Then, the uniformly dispersed solid material and molten diphenyl sulfone are sequentially introduced into the reactor. The reactants are first heated to 160-200℃ with stirring at 30-80 rpm and held at this temperature for 0.5-1.5 h; then heated to 180-220℃ and held for 0.5-1.5 h; then heated to 240-270℃ and held for 0.5-2 h. The temperature is raised to 260-290℃ and held for 0.5-2 hours to complete the salt formation reaction. Subsequently, the resulting salt solution is added together with the molten diphenyl sulfone solution of 4,4'-difluorobenzophenone into a continuous polymerization reactor, and the continuous polymerization reaction is carried out at 280-320℃ for 1-4 hours. During the salt formation reaction and the continuous polymerization reaction, pulse stirring is applied every 10-30 seconds, each lasting 10-90 seconds, and the stirring speed is adjusted to 40-120 rpm when pulse stirring is applied. The polymerization product is then cooled, pulverized, and washed to obtain crude polyether ether ketone. The compound porous sodium carbonate is composed of mesoporous sodium carbonate with a pore size of 2-50 nm and macroporous sodium carbonate with a pore size of 300-500 nm, with the proportion of mesoporous sodium carbonate being 50-80 wt.%.

[0009] Preferably, the preparation method of mesoporous sodium carbonate and macroporous sodium carbonate is as follows: An aqueous solution of sodium carbonate and a template is prepared, dried into a solid, and then washed at 130-220℃ or with an ethanol-water mixture to remove the template, thereby obtaining mesoporous sodium carbonate and macroporous sodium carbonate. The template method for preparing mesoporous and macroporous sodium carbonate results in a uniform pore structure.

[0010] Preferably, when preparing mesoporous sodium carbonate, the concentration of sodium carbonate in the aqueous solution is 1-3 mol / L, and the molar ratio of sodium carbonate to template agent is 1:(1.5-3); when preparing macroporous sodium carbonate, the concentration of sodium carbonate in the aqueous solution is 1-2 mol / L, and the molar ratio of sodium carbonate to template agent is 1:(3.5-8).

[0011] Preferably, the template is glycine, alanine, urea, glucose, sucrose, L64, P105 or Brij 35.

[0012] Compared with the use of dense sodium carbonate, light sodium carbonate, single mesoporous sodium carbonate, and single macroporous sodium carbonate, the advantages of using a compound porous sodium carbonate in this invention are: Composite porous sodium carbonate overcomes the inherent bottleneck of single-porous materials where "high specific surface area and low mass transfer resistance are difficult to achieve simultaneously." It can simultaneously achieve high active site density and high mass transfer efficiency during the salt-forming reaction stage, thereby improving the product quality of subsequent polymerization reactions through uniform salt-forming products. Dense sodium carbonate relies solely on the outer surface of the particles for salt-forming, resulting in extremely high mass transfer resistance. The water generated during salt formation easily forms a hydrate passivation layer (entanglement effect) on the particle surface, causing the reaction rate to continuously decline as the reaction progresses, ultimately leading to low salt conversion rate and poor product uniformity. While light sodium carbonate forms a porous structure through the calcination and decomposition of sodium bicarbonate, the pores are disordered, mainly consisting of blind pores and semi-connected pores. The effective reaction depth is limited to the particle surface, resulting in limited improvement in mass transfer and insignificant overall improvement in salt-forming efficiency. Although single mesoporous sodium carbonate possesses high specific surface area and abundant active sites, it still exhibits other advantages. While large-pore sodium carbonate has active sites, its small pore size leads to high internal diffusion resistance. CO2 generated during salt formation easily forms gas barriers within the pores, limiting the outward diffusion rate of in-situ generated sodium phenolate. The rate of decay is significant in the middle and later stages of the reaction, and the active sites deep within the particles cannot be fully utilized, resulting in a clear upper limit to the salt formation conversion rate. On the other hand, single-pore sodium carbonate has interconnected pores and low internal diffusion resistance, allowing CO2 byproducts to escape rapidly. It has a fast start-up rate and high site utilization, but is limited by its low specific surface area, resulting in an insufficient total number of active sites and a clear upper limit to the overall salt formation reaction capacity.

[0013] This invention employs a mesoporous sodium carbonate / macroporous sodium carbonate composite system. Through the functional division and hierarchical synergistic effect of the two types of porous particles, it achieves a significant performance improvement in the salt formation stage: macroporous particles, with their interconnected coarse pores, act as mass transfer hubs and exhaust channels within the system, rapidly removing CO2 byproducts to eliminate local gas resistance. Simultaneously, they thin the mass transfer boundary layer on the surface of mesoporous particles, reducing their external diffusion resistance and significantly enhancing their internal diffusion capacity, allowing more active sites deep within the pores to participate in the salt formation reaction. Mesoporous particles, with their high specific surface area, provide ample reactive sites, ensuring the overall salt formation reaction capacity of the system. With their synergistic effect, the salt formation reaction is rapid, and the overall reaction cycle is further shortened. At the same time, the uniformity of the reaction across the entire system is significantly improved, the concentration distribution of the salt formation product is uniform, the chain growth synchronization during subsequent polymerization is stronger, and the resulting polyetheretherketone product has a narrower molecular weight distribution, higher chain regularity, and simultaneously improved mechanical properties and thermal stability. The reduction in side reactions and residual impurities also lowers the material and energy costs of subsequent purification processes.

[0014] Preferably, the equipment used for solid-phase premixing is a ball mill, a ribbon mixer, or a twin-screw mixer.

[0015] Preferably, the molar ratio of 4,4'-difluorobenzophenone, hydroquinone, and porous sodium carbonate is (0.99-1.01):1:(1.1-1.4).

[0016] Preferably, when polyether ether ketone is synthesized by a batch method, molten diphenyl sulfone accounts for 60-70% of the total mass of the solid phase material; when polyether ether ketone is synthesized by a continuous method, the total mass of the molten diphenyl sulfone added twice accounts for 60-70% of the total mass of the polymer material (i.e., polymer monomer, porous sodium carbonate and solvent).

[0017] This invention addresses the core problems of low salt-forming efficiency, long reaction time, and poor product performance in the heterogeneous synthesis of polyether ether ketones (PEEK). Through the customized design of a composite porous sodium carbonate salt-forming agent consisting of uniform mesoporous sodium carbonate and macroporous sodium carbonate, combined with synergistic mixing via pulse stirring, it overcomes the technical bottlenecks of heterogeneous reactions from multiple dimensions, including mass transfer within micropores, macroscopic system mixing, and reaction kinetic matching. Compared with existing processes for dense sodium carbonate, light sodium carbonate, and single-pore porous sodium carbonate, it possesses the following significant advantages: 1. This invention employs a composite porous sodium carbonate of uniform mesoporous sodium carbonate and macroporous sodium carbonate to replace traditional dense sodium carbonate and light sodium carbonate as salt-forming agents. Mesoporous sodium carbonate, with its high specific surface area, provides ample active reaction sites, ensuring the overall reaction capacity of the system. Macroporous sodium carbonate acts as a mass transfer hub and venting channel within the system, rapidly removing products while thinning the mass transfer boundary layer on the surface of mesoporous particles, reducing the mass transfer resistance of the mesoporous material and further improving the utilization rate of the active sites of the mesoporous particles. The mesoporous / macroporous sodium carbonate composite system, through hierarchical mass transfer synergy, significantly reduces the mass transfer resistance of heterogeneous salt-forming reactions. The rate-limiting step shifts from being primarily controlled by mass transfer to being primarily controlled by surface reaction, with the reaction rate approaching the level of reaction kinetics. This solves the limitations of low mass transfer efficiency and surface-only reaction capabilities of dense sodium carbonate and light sodium carbonate, and also compensates for the shortcomings of insufficient active sites in single macroporous sodium carbonate and the tendency for clogging and degradation in the later stages of single mesoporous sodium carbonate. Combined with pulse stirring technology in the salt formation and polymerization stages, instantaneous turbulence further enhances solid-liquid mixing and eliminates mass transfer dead zones. Compared with the traditional dense sodium carbonate process, it can shorten the total synthesis cycle by about 15% and improve the efficiency of industrial production.

[0018] 2. This invention utilizes a nitrogen-protected raw material premixing process to achieve uniform dispersion of hydroquinone, compound porous sodium carbonate, or their combination with 4,4'-difluorobenzophenone. This avoids the problem of localized overconcentration of reactants caused by batch-by-batch feeding from the outset, reducing the occurrence of side reactions such as etherification and oxidation. Simultaneously, pulse stirring is employed during the salt formation and polymerization stages. The resulting instantaneous turbulence eliminates dead zones in the reactor, ensuring uniform dispersion of solid particles throughout the molten solvent. This guarantees synchronous and uniform salt formation reactions in all areas of the reactor, resulting in consistent concentrations of the generated hydroquinone sodium. The uniform salt formation product provides a stable reaction foundation for subsequent polymerization, avoiding uneven polymer chain lengths caused by localized polymerization rate differences. The final crude polyether ether ketone (PEEK) product exhibits a further reduced molecular weight distribution (PDI), significantly superior to products from traditional processes, greatly improving batch stability and processing compatibility.

[0019] 3. The high reactivity of the compound porous sodium carbonate and the efficient mixing of pulse stirring in this invention combine to achieve a more complete salt formation reaction between hydroquinone and sodium carbonate, significantly reducing the residue of unreacted hydroquinone and its oxidation products, minimizing interference from impurities in the polymerization reaction, and improving the monomer polymerization conversion rate. Simultaneously, the effective suppression of side reactions prevents the destruction of polymer chain structure by low-molecular-weight byproducts, resulting in higher regularity of the polyetheretherketone (PEEK) molecular chains. The final crude PEEK exhibits significantly improved mechanical properties, with a tensile strength exceeding 106 MPa, representing an improvement over products prepared using traditional processes. The overall performance of the product better meets the high-performance application requirements of aerospace, high-end manufacturing, and other fields.

[0020] 4. This invention designs batch and continuous reaction processes suitable for industrial production. Both processes retain the core technical features of raw material premixing, pulse stirring, and compounding porous sodium carbonate to form salts. Furthermore, the reaction temperature, stirring speed, and pulse parameters are precisely controlled, further optimizing the polymer chain growth process and balancing production efficiency and product performance.

[0021] 5. This invention reduces side reactions from the source by premixing raw materials and ensuring uniform reaction. The high conversion rate of the salt formation reaction also reduces the residue of unreacted raw materials, resulting in a significant reduction in the types and amounts of impurities in the reaction products. In the subsequent product purification process, the amount of washing solvents such as acetone and water can be reduced, while the washing and drying process time is shortened, reducing material and energy costs in the purification stage. In addition, the reduction of impurities also reduces the generation of waste during the purification process, making the synthesis process of polyetheretherketone (PEEK) greener and more economical.

[0022] In summary, the heterogeneous reaction process of this invention achieves a technological upgrade in polyetheretherketone (PEEK) synthesis from multiple aspects, including salt-forming agent modification, mixing method optimization, and process route design. It not only solves the core pain points of existing technologies but also takes into account the efficiency, cost, and adaptability of industrial production. The prepared PEEK products have excellent performance and batch stability, providing a new feasible solution for the efficient, high-performance, and large-scale synthesis of PEEK, and has significant technological innovation and industrial application value. Attached Figure Description

[0023] Figure 1 This is a TEM image of the mesoporous sodium carbonate prepared in Example 1 of this invention.

[0024] Figure 2 This is a BET diagram of the mesoporous sodium carbonate prepared in Example 1 of this invention.

[0025] Figure 3 This is a mercury porosimetry diagram of macroporous sodium carbonate prepared in Example 1 of the present invention. Detailed Implementation

[0026] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention.

[0027] Example 1 The process for synthesizing polyetheretherketone using compound porous sodium carbonate in this embodiment includes the following steps: S1 Preparation of Composite Porous Sodium Carbonate Mesoporous sodium carbonate: An aqueous solution of sodium carbonate and glycine was prepared, with a sodium carbonate concentration of 1 mol / L and a glycine concentration of 2 mol / L. The solution was transferred to a 60°C oven and dried until a white solid was obtained. Subsequently, it was washed with an ethanol-water mixture at 0°C to remove glycine, yielding mesoporous sodium carbonate. Its transmission electron microscopy (TEM) morphology is shown below. Figure 1 As shown, according to the scale calculation, the average pore size of the obtained mesoporous sodium carbonate is approximately 8 nm; BET results are as follows. Figure 2 As shown, the differential pore size distribution curve has 8 nm as the most probable pore size; the pore size range covers 3-20 nm, and there are significant pore volume responses in the 3-8 nm and 8-20 nm ranges, confirming that the material has a multi-level mesoporous structure and that mesopores of various sizes coexist.

[0028] Macroporous sodium carbonate: Prepare an aqueous solution of sodium carbonate and urea, wherein the concentration of sodium carbonate is 1 mol / L and the concentration of urea is 5 mol / L. Transfer the solution to a 60°C oven and dry until a white solid is obtained. Then, raise the oven temperature to 180°C to remove the urea, yielding macroporous sodium carbonate. Its mercury porosimetry diagram is shown below. Figure 3 As shown, its average pore size is approximately 360 nm, indicating a macroporous structure.

[0029] The prepared mesoporous sodium carbonate and macroporous sodium carbonate were mixed at a mass ratio of 7:3 to obtain compound porous sodium carbonate.

[0030] S2 batch method for synthesizing polyetheretherketone Under a nitrogen-protected atmosphere, 4,4'-difluorobenzophenone, hydroquinone, and the composite porous sodium carbonate prepared in step S1 were homogeneously mixed in a ribbon mixer. The molar ratio of 4,4'-difluorobenzophenone, hydroquinone, and composite porous sodium carbonate was 1:1:1.2. Subsequently, the uniformly dispersed solid material and 65% by mass of molten diphenyl sulfone solvent were sequentially added to the reactor. The mixture was heated to 180°C with a stirring speed of 50 rpm and held for 1 hour to form a homogeneous reaction mixture. The temperature was then increased to 200°C and held for 1 hour, then increased to 250°C and held for 1 hour, then increased to 270°C and held for 1 hour, and finally increased to 310°C and held for 2 hours to terminate the polymerization reaction. Throughout the reaction, pulse stirring was applied every 20 seconds for 30 seconds, with the stirring speed adjusted to 80 rpm during each pulse. After the reaction was completed, the product was cooled, pulverized, and washed with acetone and water to finally obtain crude PEEK.

[0031] Comparative Example 1 The difference from Example 1 is that in step S2, 4,4'-difluorobenzophenone, hydroquinone, and the compound porous sodium carbonate prepared in step S1 are not premixed. Instead, 4,4'-difluorobenzophenone, hydroquinone, compound porous sodium carbonate, and molten diphenyl sulfone solvent are directly added to the reactor and heated to 180°C with a stirring speed of 50 rpm and kept at that temperature for 1 hour to form a homogeneous reaction mixture. Other operations are the same as in Example 1.

[0032] Comparative Example 2 The difference from Example 1 is that in step S2, the entire reaction process is carried out at a stirring speed of 80 rpm without applying pulses.

[0033] Comparative Example 3 The difference from Example 1 is that commercially available non-porous dense sodium carbonate is used instead of the compound porous sodium carbonate prepared in step S1.

[0034] Comparative Example 4 The difference from Example 1 is that light sodium carbonate is used instead of the compound porous sodium carbonate prepared in step S1. The preparation method of light sodium carbonate is as follows: sodium bicarbonate is ball-milled, and then the ball-milled sodium bicarbonate is placed in a reaction vessel and heated to 180°C at a rate of 5°C / min. After holding at the temperature for 1 hour, light sodium carbonate is obtained.

[0035] Comparative Example 5 The difference from Example 1 is that mesoporous sodium carbonate prepared in step S1 is used instead of compounded porous sodium carbonate.

[0036] Comparative Example 6 The difference from Example 1 is that macroporous sodium carbonate prepared in step S1 is used instead of compounded porous sodium carbonate.

[0037] Example 2 The process for synthesizing polyetheretherketone using compound porous sodium carbonate in this embodiment includes the following steps: S1 Preparation of Composite Porous Sodium Carbonate Mesoporous sodium carbonate: Prepare an aqueous solution of sodium carbonate and glycine, wherein the concentration of sodium carbonate is 1 mol / L and the concentration of glycine is 1.5 mol / L. Transfer the solution to a 60°C oven and dry until a white solid is obtained. Then, wash the solid with an ethanol-water mixture at 0°C to remove the glycine, thus obtaining mesoporous sodium carbonate.

[0038] Macroporous sodium carbonate: Prepare an aqueous solution of sodium carbonate and urea, wherein the concentration of sodium carbonate is 1 mol / L and the concentration of urea is 7 mol / L. Transfer the solution to an oven at 60°C and dry until a white solid is obtained. Then, raise the oven temperature to 180°C to remove the urea, and obtain macroporous sodium carbonate.

[0039] The prepared mesoporous sodium carbonate and macroporous sodium carbonate were mixed at a mass ratio of 5:5 to obtain compound porous sodium carbonate.

[0040] S2 batch method for synthesizing polyetheretherketone Under a nitrogen-containing atmosphere, 4,4'-difluorobenzophenone, hydroquinone, and the composite porous sodium carbonate prepared in step S1 were homogeneously mixed in a ball mill. The molar ratio of 4,4'-difluorobenzophenone, hydroquinone, and composite porous sodium carbonate was 0.99:1:1.1. Subsequently, the uniformly dispersed solid material and 60% by mass of molten diphenyl sulfone solvent were added sequentially to the reactor. The mixture was heated to 160°C with a stirring speed of 30 rpm and held for 1.5 h to form a homogeneous reaction mixture. The temperature was then increased to 180°C and held for 1.5 h, then increased to 240°C and held for 2 h, then increased to 260°C and held for 2 h, and finally increased to 300°C and held for 3.5 h to terminate the polymerization reaction. Throughout the reaction, pulse stirring was applied every 10 s for 30 s, with the stirring speed adjusted to 80 rpm during each pulse. After the reaction was completed, the product was cooled, pulverized, and washed with acetone and water to finally obtain crude PEEK.

[0041] Comparative Example 7 The difference from Example 2 is that in step S2, 4,4'-difluorobenzophenone, hydroquinone, and the compound porous sodium carbonate prepared in step S1 are not premixed. Instead, 4,4'-difluorobenzophenone, hydroquinone, compound porous sodium carbonate, and molten diphenyl sulfone solvent are directly added to the reactor and heated to 160°C with a stirring speed of 30 rpm, and kept at this temperature for 1.5 h to form a homogeneous reaction material. Other operations are the same as in Example 2.

[0042] Comparative Example 8 The difference from Example 2 is that in step S2, the entire reaction process is carried out at a stirring speed of 80 rpm without applying pulses.

[0043] Comparative Example 9 The difference from Example 2 is that commercially available non-porous dense sodium carbonate is used instead of the compound porous sodium carbonate prepared in step S1.

[0044] Example 3 The process for synthesizing polyetheretherketone using compound porous sodium carbonate in this embodiment includes the following steps: S1 Preparation of Composite Porous Sodium Carbonate Mesoporous sodium carbonate: Prepare an aqueous solution of sodium carbonate and glycine, wherein the concentration of sodium carbonate is 1 mol / L and the concentration of glycine is 2 mol / L. Transfer the solution to a 60°C oven and dry until a white solid is obtained. Then, wash the solid with an ethanol-water mixture at 0°C to remove the glycine, thus obtaining mesoporous sodium carbonate.

[0045] Macroporous sodium carbonate: Prepare an aqueous solution of sodium carbonate and urea, wherein the concentration of sodium carbonate is 1 mol / L and the concentration of urea is 5 mol / L. Transfer the solution to an oven at 60°C and dry until a white solid is obtained. Then, raise the oven temperature to 220°C to remove the urea, thereby obtaining macroporous sodium carbonate.

[0046] The prepared mesoporous sodium carbonate and macroporous sodium carbonate were mixed at a mass ratio of 8:2 to obtain compound porous sodium carbonate.

[0047] S2 batch method for synthesizing polyetheretherketone Under a nitrogen-protected atmosphere, 4,4'-difluorobenzophenone, hydroquinone, and the composite porous sodium carbonate prepared in step S1 were homogeneously mixed in a twin-screw mixer. The molar ratio of 4,4'-difluorobenzophenone, hydroquinone, and composite porous sodium carbonate was 1.01:1:1.4. Subsequently, the uniformly dispersed solid material and molten diphenyl sulfone solvent (70% by mass of the solid material) were sequentially added to the reactor. The mixture was heated to 200°C with stirring at 80 rpm and held for 0.5 h to form a homogeneous reaction mixture. The temperature was then increased to 220°C and held for 0.5 h, then increased to 270°C and held for 0.5 h, then increased to 290°C and held for 0.5 h, and finally increased to 320°C and held for 1 h to terminate the polymerization reaction. Throughout the reaction, pulse stirring was applied every 30 seconds for 30 seconds, with the stirring speed adjusted to 80 rpm during each pulse. After the reaction was completed, the product was cooled, pulverized, and washed with acetone and water to finally obtain crude PEEK.

[0048] Comparative Example 10 The difference from Example 3 is that in step S2, 4,4'-difluorobenzophenone, hydroquinone, and the compound porous sodium carbonate prepared in step S1 are not premixed. Instead, 4,4'-difluorobenzophenone, hydroquinone, compound porous sodium carbonate, and molten diphenyl sulfone solvent are directly added to the reactor and heated to 200°C with stirring at 80 rpm and kept at that temperature for 0.5 h to form a homogeneous reaction mixture. Other operations are the same as in Example 3.

[0049] Comparative Example 11 The difference from Example 3 is that in step S2, the entire reaction process is carried out at a stirring speed of 80 rpm without applying pulses.

[0050] Comparative Example 12 The difference from Example 3 is that commercially available non-porous dense sodium carbonate is used instead of the compound porous sodium carbonate prepared in step S1.

[0051] Example 4 The process for synthesizing polyetheretherketone using compound porous sodium carbonate in this embodiment includes the following steps: S1 Preparation of Composite Porous Sodium Carbonate Mesoporous sodium carbonate: Prepare an aqueous solution of sodium carbonate and glycine, wherein the concentration of sodium carbonate is 1 mol / L and the concentration of glycine is 2 mol / L. Transfer the solution to a 60°C oven and dry until a white solid is obtained. Then, wash the solid with an ethanol-water mixture at 0°C to remove the glycine, thus obtaining mesoporous sodium carbonate.

[0052] Macroporous sodium carbonate: Prepare an aqueous solution of sodium carbonate and urea, wherein the concentration of sodium carbonate is 1 mol / L and the concentration of urea is 5 mol / L. Transfer the solution to an oven at 60°C and dry until a white solid is obtained. Then, raise the oven temperature to 180°C to remove the urea, thus obtaining macroporous sodium carbonate.

[0053] The prepared mesoporous sodium carbonate and macroporous sodium carbonate were mixed at a mass ratio of 7:3 to obtain compound porous sodium carbonate.

[0054] S2 continuous method for the synthesis of polyetheretherketone Under a nitrogen-protected atmosphere, hydroquinone and compound porous sodium carbonate were premixed in a ribbon mixer and then added sequentially to a salt-forming reactor along with molten diphenyl sulfone. The molar ratio of hydroquinone to compound porous sodium carbonate was 1:1.2. The reactants were then heated to 180°C at 50 rpm and held for 1 hour, followed by a further increase to 200°C and holding for 1 hour, then to 250°C and holding for 1 hour, and finally to 280°C and holding for 1 hour to complete the salt-forming reaction. The resulting salt solution was then added together with a molten diphenyl sulfone solution of 4,4'-difluorobenzophenone to hydroquinone in a continuous polymerization reactor and continuously polymerized at 310°C for 2 hours. The molar ratio of 4,4'-difluorobenzophenone to hydroquinone was 1:1, and the total mass of the molten diphenyl sulfone added in both reactions accounted for 65% of the total mass of the polymer. During the salt formation and continuous polymerization reactions, pulse stirring was applied every 20 seconds for 30 seconds each time, with the stirring speed adjusted to 80 rpm during the pulse. After the reaction was completed, the product was cooled, pulverized, and washed with acetone and water to finally obtain crude PEEK.

[0055] Comparative Example 13 The difference from Example 4 is that in step S2, hydroquinone and the compound porous sodium carbonate are not premixed in a solid phase, and hydroquinone, the compound porous sodium carbonate and the molten diphenyl sulfone solvent are directly added to the salt-forming reactor; other operations are the same as in Example 4.

[0056] Comparative Example 14 The difference from Example 4 is that in step S2, the entire salt formation reaction and continuous polymerization reaction process are carried out at a stirring speed of 80 rpm without applying pulses.

[0057] Comparative Example 15 The difference from Example 4 is that commercially available non-porous dense sodium carbonate is used instead of the compound porous sodium carbonate prepared in step S1.

[0058] Comparative Example 16 The difference from Example 4 is that in step S2, pulse stirring is applied every 20 seconds, each lasting 10 seconds, and the stirring speed is adjusted to 120 rpm when the pulse is applied.

[0059] Comparative Example 17 The difference from Example 4 is that in step S2, pulse stirring is applied every 20 seconds, each lasting 30 seconds, and the stirring speed is adjusted to 60 rpm when the pulse is applied.

[0060] Example 5 The process for synthesizing polyetheretherketone using compound porous sodium carbonate in this embodiment includes the following steps: S1 Preparation of Composite Porous Sodium Carbonate Mesoporous sodium carbonate: Prepare an aqueous solution of sodium carbonate and glycine, wherein the concentration of sodium carbonate is 1 mol / L and the concentration of glycine is 1.5 mol / L. Transfer the solution to a 60°C oven and dry until a white solid is obtained. Then, wash the solid with an ethanol-water mixture at 0°C to remove the glycine, thus obtaining mesoporous sodium carbonate.

[0061] Macroporous sodium carbonate: Prepare an aqueous solution of sodium carbonate and urea, wherein the concentration of sodium carbonate is 1 mol / L and the concentration of urea is 7 mol / L. Transfer the solution to an oven at 60°C and dry until a white solid is obtained. Then, raise the oven temperature to 180°C to remove the urea, and obtain macroporous sodium carbonate.

[0062] The prepared mesoporous sodium carbonate and macroporous sodium carbonate were mixed at a mass ratio of 5:5 to obtain compound porous sodium carbonate.

[0063] S2 continuous method for the synthesis of polyetheretherketone Under a nitrogen-protected atmosphere, hydroquinone and compound porous sodium carbonate were premixed in a ribbon mixer and then added sequentially to a salt-forming reactor along with molten diphenyl sulfone. The molar ratio of hydroquinone to compound porous sodium carbonate was 1:1.2. The reactants were then heated to 160°C at 30 rpm and held for 1.5 h, followed by a further increase to 180°C and holding for 1.5 h, then to 240°C and holding for 2 h, and finally to 260°C and holding for 2 h to complete the salt-forming reaction. The resulting salt solution was then added together with a molten diphenyl sulfone solution of 4,4'-difluorobenzophenone to hydroquinone in a continuous polymerization reactor and continuously polymerized at 300°C for 3.5 h. The molar ratio of 4,4'-difluorobenzophenone to hydroquinone was 1:1, and the total mass of the molten diphenyl sulfone added in both reactions accounted for 65% of the total mass of the polymer. During the salt formation and continuous polymerization reactions, pulse stirring was applied every 10 seconds for 30 seconds each time, with the stirring speed adjusted to 80 rpm during the pulse. After the reaction was completed, the product was cooled, pulverized, and washed with acetone and water to finally obtain crude PEEK.

[0064] Comparative Example 18 The difference from Example 5 is that in step S2, hydroquinone and the compound porous sodium carbonate are not premixed in a solid phase, and hydroquinone, the compound porous sodium carbonate and the molten diphenyl sulfone solvent are directly added to the salt-forming reactor; other operations are the same as in Example 5.

[0065] Comparative Example 19 The difference from Example 5 is that in step S2, the entire salt formation reaction and continuous polymerization reaction process are carried out at a stirring speed of 80 rpm without applying pulses.

[0066] Comparative Example 20 The difference from Example 5 is that commercially available non-porous dense sodium carbonate is used instead of the compound porous sodium carbonate prepared in step S1.

[0067] Example 6 The process for synthesizing polyetheretherketone using compound porous sodium carbonate in this embodiment includes the following steps: S1 Preparation of Composite Porous Sodium Carbonate Mesoporous sodium carbonate: Prepare an aqueous solution of sodium carbonate and alanine, wherein the concentration of sodium carbonate is 1 mol / L and the concentration of alanine is 2 mol / L. Transfer the solution to a 60°C oven and dry until a white solid is obtained. Then, wash the solid with an ethanol-water mixture at 0°C to remove the alanine, thus obtaining mesoporous sodium carbonate.

[0068] Macroporous sodium carbonate: Prepare an aqueous solution of sodium carbonate and L64, wherein the concentration of sodium carbonate is 1 mol / L and the concentration of L64 is 5 mol / L. Transfer the solution to an oven at 60°C and dry until a white solid is obtained. Then, heat the oven to 180°C to remove L64, obtaining macroporous sodium carbonate.

[0069] The prepared mesoporous sodium carbonate and macroporous sodium carbonate were mixed at a mass ratio of 8:2 to obtain compound porous sodium carbonate.

[0070] S2 continuous method for the synthesis of polyetheretherketone Under a nitrogen-protected atmosphere, hydroquinone and compound porous sodium carbonate were premixed in a ball mill and then added sequentially to a salt-forming reactor along with molten diphenyl sulfone. The molar ratio of hydroquinone to compound porous sodium carbonate was 1:1.2. The reactants were then heated to 200°C with stirring at 80 rpm and held for 0.5 h, followed by a further increase to 220°C and holding for 0.5 h, then to 270°C and holding for 0.5 h, and finally to 290°C and holding for 0.5 h to complete the salt-forming reaction. The resulting salt solution was then added together with a molten diphenyl sulfone solution of 4,4'-difluorobenzophenone to hydroquinone solution to a continuous polymerization reactor and continuously polymerized at 320°C for 1 h. The molar ratio of 4,4'-difluorobenzophenone to hydroquinone was 1:1, and the total mass of the molten diphenyl sulfone added in both reactions accounted for 65% of the total mass of the polymer. During the salt formation and continuous polymerization reactions, pulse stirring was applied every 30 seconds, with each pulse lasting 30 seconds. The stirring speed was adjusted to 80 rpm during the pulse. After the reaction, the product was cooled, pulverized, and washed with acetone and water to obtain crude PEEK.

[0071] Comparative Example 21 The difference from Example 6 is that in step S2, hydroquinone and the compound porous sodium carbonate are not premixed in a solid phase, and hydroquinone, the compound porous sodium carbonate and the molten diphenyl sulfone solvent are directly added to the salt-forming reactor; other operations are the same as in Example 6.

[0072] Comparative Example 22 The difference from Example 6 is that in step S2, the entire salt formation reaction and continuous polymerization reaction process are carried out at a stirring speed of 80 rpm without applying pulses.

[0073] Comparative Example 23 The difference from Example 6 is that commercially available non-porous dense sodium carbonate is used instead of the compound porous sodium carbonate prepared in step S1.

[0074] The performance of the crude polyetheretherketone synthesized in Examples 1-6 and Comparative Examples 1-23 was tested, and the test results are shown in Table 1: Table 1. Reaction times and performance test results of the synthesized crude polyether ether ketones in Examples 1-6 and Comparative Examples 1-23

[0075] The results in Table 1 show that this invention, through the design of a compound porous sodium carbonate salt-forming agent, coupled with multi-dimensional technical means such as pulse stirring to enhance mixing and solid-phase premixing and homogenization feeding, forms a complete enhanced chain from mass transfer within micropores and macroscopic system mixing to polymerization process control. This systematically overcomes the technical bottlenecks of low salt-forming efficiency, long reaction cycle, and wide molecular weight distribution of products in traditional PEEK heterogeneous synthesis. In the compound porous sodium carbonate, the high specific surface area provided by the mesoporous structure ensures sufficient active sites for the salt-forming reaction, while the rapid mass transfer and degassing network constructed by the macroporous channels quickly initiates the salt-forming reaction and effectively inhibits pore blockage and activity decay in the later stages of the reaction. The compound porous sodium carbonate effectively weakens the mass transfer resistance bottleneck of the solid-liquid reaction, enabling the salt-forming reaction to shift from a mass transfer-dominated to a kinetic-dominated stage, significantly improving reaction efficiency. The instantaneous turbulence generated by pulse stirring further eliminates mass transfer dead zones in the reaction system, and the solid-phase premixing process ensures the synchronicity of the reaction throughout the entire process, narrowing the polymer molecular weight distribution at the process level. The continuous reaction mode further optimizes the chain growth process through stable material concentration and temperature field, ultimately achieving a dual improvement in reaction efficiency and product performance. Under optimal process conditions, the PEEK synthesis cycle is shortened by approximately 15% compared to the traditional dense sodium carbonate process, the tensile strength of the product exceeds 106 MPa, and the molecular weight distribution index can be as low as 1.80. Simultaneously, the reduction in impurity content simplifies post-processing steps, balancing production efficiency, product performance, and manufacturing costs. This provides a practical and feasible new technical solution for the high-performance, large-scale, and green synthesis of polyetheretherketone (PEEK).

Claims

1. A process for synthesizing polyetheretherketone using a compound porous sodium carbonate, characterized in that, When synthesizing polyetheretherketone (PEEK) using a batch method, hydroquinone, compounded porous sodium carbonate, and 4,4'-difluorobenzophenone are premixed in a solid phase under nitrogen protection. The uniformly dispersed solid material and molten diphenyl sulfone are then sequentially introduced into the reactor. The reaction mixture is first heated to 160-200℃ at a stirring speed of 30-80 rpm and held for 0.5-1.5 h; then heated to 180-220℃ and held for 0.5-1.5 h; then heated to 240-270℃ and held for 0.5-2 h; then heated to 260-290℃ and held for 0.5-2 h; finally, heated to 300-320℃ and held for 1-3.5 h to complete the polymerization reaction. During this process, pulse stirring is applied every 10-30 s, each lasting 10-90 s, and the stirring speed is adjusted to 40-120 rpm during pulse stirring to generate instantaneous turbulence. When synthesizing polyetheretherketone (PEEK) using a continuous method, hydroquinone and a compound porous sodium carbonate are premixed in a solid phase under nitrogen protection. Then, the uniformly dispersed solid material and molten diphenyl sulfone are sequentially introduced into the reactor. The reactants are first heated to 160-200℃ with stirring at 30-80 rpm and held at this temperature for 0.5-1.5 h; then heated to 180-220℃ and held for 0.5-1.5 h; then heated to 240-270℃ and held for 0.5-2 h. The temperature is raised to 260-290℃ and held for 0.5-2 hours to complete the salt formation reaction. Subsequently, the resulting salt solution is added together with the molten diphenyl sulfone solution of 4,4'-difluorobenzophenone into a continuous polymerization reactor, and the continuous polymerization reaction is carried out at 280-320℃ for 1-4 hours. During the salt formation reaction and the continuous polymerization reaction, pulse stirring is applied every 10-30 seconds, each lasting 10-90 seconds, and the stirring speed is adjusted to 40-120 rpm when pulse stirring is applied. The polymerization product is then cooled, pulverized, and washed to obtain crude polyether ether ketone. The compound porous sodium carbonate is composed of mesoporous sodium carbonate with a pore size of 2-50 nm and macroporous sodium carbonate with a pore size of 300-500 nm, with the proportion of mesoporous sodium carbonate being 50-80 wt.%.

2. The process for synthesizing polyetheretherketone using compound porous sodium carbonate as described in claim 1, characterized in that, The preparation methods of mesoporous sodium carbonate and macroporous sodium carbonate are as follows: prepare an aqueous solution of sodium carbonate and template, dry it into a solid, and then wash it at 130-220℃ or with an ethanol-water mixture to remove the template, thereby obtaining mesoporous sodium carbonate and macroporous sodium carbonate.

3. The process for synthesizing polyetheretherketone using compound porous sodium carbonate as described in claim 2, characterized in that, When preparing mesoporous sodium carbonate, the concentration of sodium carbonate in the aqueous solution is 1-3 mol / L, and the molar ratio of sodium carbonate to template agent is 1:(1.5-3); when preparing macroporous sodium carbonate, the concentration of sodium carbonate in the aqueous solution is 1-2 mol / L, and the molar ratio of sodium carbonate to template agent is 1:(3.5-8).

4. The process for synthesizing polyetheretherketone using compound porous sodium carbonate as described in claim 2, characterized in that, The template is glycine, alanine, urea, glucose, or sucrose.

5. The process for synthesizing polyetheretherketone using compound porous sodium carbonate as described in claim 1, characterized in that, The equipment used for solid-phase premixing is a ball mill, ribbon mixer, or twin-screw mixer.

6. The process for synthesizing polyetheretherketone using compound porous sodium carbonate as described in claim 1, characterized in that, The molar ratio of 4,4'-difluorobenzophenone, hydroquinone, and porous sodium carbonate is (0.99-1.01):1:(1.1-1.4).

7. The process for synthesizing polyetheretherketone using compound porous sodium carbonate as described in claim 1, characterized in that, When polyether ether ketone is synthesized using a batch method, molten diphenyl sulfone accounts for 60-70% of the total mass of the solid phase material; when polyether ether ketone is synthesized using a continuous method, the total mass of the molten diphenyl sulfone added twice accounts for 60-70% of the total mass of the polymer material.

Citation Information

Patent Citations

  • A method for synthesizing polyetheretherketone

    CN114437338B

  • Synthesis method of polyether-ether-ketone

    CN115612092A

  • Method for preparing poly (aryl ether ketone) and poly (aryl ether ketone)

    CN113563578A

  • Synthesis method of polyether-ether-ketone

    CN114437338A